Lead, Land, and Cranberries: The Ho-Chunk Experience in the 19th Century - King, Adam (My University, 2011)
This paper will examine how and why the Ho-Chunk people of Wisconsin lost their estate in Wisconsin. The paper will focus on the desire for natural resources that drove white settlers to push for the removal of the Ho-Chunk people from Wisconsin. The paper will build on the work of other historians to tell a more complete story of the Ho-Chunk experience. Specifically the paper will closely examine a long overlooked part of Ho-Chunk history, the removal of 1873. By telling this story in more detail I hope to complete the history of the Ho-Chunk in the 19th century.
Keywords: Ho Chunk Indians--Land tenure--Wisconsin; Ho Chunk Indians--Relocation--Wisconsin; Ho Chunk Indians--Government relations; Indians of North America--Wisconsin--Government relations; Indians of North America--Government relations--1869-1934